Evaluation of Supplementation of Ashgourd Fermented Beverage to Geriatric Population - C.S. Devaki; K.S. Premavalli (Journal of Pharmacy and Nutrition Sciences, 2012)
Existing data indicates a significant morbidity among the aged and most may remain subclinical. Vegetables being good source of vitamins and minerals, further their concentration has been improved by fermentation process. In recent years elderly institutions are being more common and a need for nutritional studies to provide better service. Thus the present study was conducted on geriatrics population to see the effect of ashgourd fermented beverage on anthropometric, nutritional and biochemical status of institutional elderly inmates. Ashgourd Fermented beverage (180ml) was provided to inmates of experimental group with the instructions to drink in fasting condition as a first drink in the morning for 60 days and control group received no supplementation. The parameters which were selected to evaluate the effect of ashgourd fermented beverage were anthropometric data, nutritional status, dietary pattern, clinical, biochemical parameters such as fasting and post prandial blood glucose levels, lipid profile, haemoglobin level and medical histories of the inmates. The selected parameters were assessed before and after the supplementation to see the effect of fermented beverage. It can be concluded from the present study that supplementation of fermented beverage showed significant improvement in BMI grades, heamoglobin and reduced blood glucose level, triglycerides and improved HDL cholesterol levels in experimental group when compared with the control group.